(untitled) (Research, Society and Development, 2020)
The districts Coqueiral and Bom Jardim, located in Nobres - MT have several natural beauties, which attract tourists from Brazil and the world. In these attractions, field classes are also held, however, the teachers do not have didactic material with information from the area to assist in planning the classes. The information produced here makes up a didactic guide built as one of the requirements for completing the professional master’s degree in professional and technological education (ProfEPT). Considering that these attractions are relevant to the local socioeconomic development and, therefore, they need to be explored in a sustainable way. Thus, this work aims to generate, analyze and describe the morphometric data and cartographic products of the physical environment of the Upper Hydrographic Basin of the Cuiabá River, where the tourist attractions linked to the two districts are located, thus contributing to studies that support the realization of didactic / pedagogical activities in tourist attractions by teachers who work in schools in the region and also with the planning of actions aimed at sustainable tourism practiced in these spaces. Field and bibliographic surveys and compiled data were necessary in the production of thematic maps of location, slope, hypsometry, vegetation, soils, hydrography, geology and geomorphology. The results show that the region has a great potential to consolidate itself as a destination for pedagogical tourism in Mato Grosso, considering that the local biodiversity provides numerous possibilities for learning in these attractions.